Direct and indirect effects of PGF2α administration in male wistar rats based on increased expression of α-SMA and androgen receptor - Teuku Armansyah; Husnurrizal Husnurrizal; Sri Wahyuni; Hafizuddin Hafizuddin; Tongku Nizwan Siregar; Amalia Sutriana; Arman Sayuti; Adinda Tri Syahrani; Muhammad Bintang Pariansyah (Open Veterinary Journal)
Background: PGF2α hormone administration can improve semen quality through increased contractility of smooth muscle cells in testicular tissue and increased testosterone hormone. Immunohistochemically, the increase in contractility of smooth muscle cells and testosterone hormone can be measured by an increase in the expression of alpha-smooth muscle actin (α-SMA) and androgen receptor (AR).